ANALYSIS OF THE PERCEPTIONS OF KPI STUDENTS FROM IAIN PONOROGO CLASS OF 2020 REGARDING CITIZEN JOURNALISM NEWS CONTENT ON INSTAGRAM @INFOPONOROGO - Nazila Aisy Zahra (QAULAN: Journal of Islamic Communication, 2024)
Citizen journalism is a new phenomenon in the world of digital and print news reporting. Instagram, a social media platform, has become a space where non-professional journalists can contribute by gathering, compiling, and disseminating news through online media. The Instagram account @infoponorogo features a significant amount of citizen journalism news content. This has led to various new perceptions, particularly among the Islamic Communication and Broadcasting (KPI) students of the 2020 cohort at IAIN Ponorogo. Therefore, it is necessary to conduct research to analyze the perceptions of students regarding citizen journalism news content on the Instagram account @infoponorogo. The findings of this research are twofold. First, the factors influencing students' perceptions are external, such as the surrounding environment, the virality of a news item, cultural background, personal background, and individual experiences of each student. Second, the form of perception developed among the students is predominantly positive.